Retail macro-location factors: empirical evidence from the portuguese shopping centres - Ribeiro, J. Cadima (2003)
Shopping centres appeared in Portugal in the beginning of the 1970’s and have expanded their presence from the eighties onwards. However, few efforts have been made to identify the macro level factors that influenced the location of Portuguese shopping centres. This study attempts to fill this gap by focusing on the region-specific endowments that motivate promoters of shopping centres to invest in a particular location. Using OLS Regression, we tested five hypotheses as pointed out by the theory, namely the population (measured by the population/area), the economy (measured by the purchasing power index), the competition (measured by the number of retailers per head), the accessibility to the shopping centre (measured by the difference between the maximum and minimum altitude) and costs (measured by the average time distance). The results support all our hypotheses, except accessibility. The population hypothesis (H1) was supported, promoters tended to invest in regions where population density is higher. The economy hypothesis was supported (H2), promoters tended to invest in high income regions. The competition hypothesis was supported (H3), promoters tended to choose regions where there is a lack of retailers per head. Finally, the cost hypothesis was also supported (H5), promoters tended to choose regions where they perceived low levels of cost. We found no support for the accessibility measure (H4), although the variable was correctly signed.